Applied imagery for motivation: a person-centred model. Issue 6 (2nd November 2022) - Rhodes, Jonathan; May, Jon
ABSTRACT: Motor imagery when coupled with motivational and cognitive factors has been shown to enhance multiple aspects of sports performance. This paper reviews existing imagery approaches, and proposes a method based on applied applications, intended to increase short and long-term motivation. Behavioural change is achieved by primarily using motivational interviewing (MI), then functional imagery training (FIT), which has been adapted into the applied imagery for motivation (AIM) model. AIM starts with an initial interview using MI, then has three imagery phases: macro imagery (beliefs, values and purposeful long-term goal), meso-imagery (mentally contrasting between current and future-self to evoke change), and micro imagery (planning for immediate action). We explain the use of these three stages which allow athletes to link everyday cues with imagery activation and immediate implementation action plans. We provide practitioners with a comprehensive applied guide to using AIM for performance, merging theory-driven established cognitive and motivational imagery approaches into structured practise.